(untitled) (Research, Society and Development, 2025)
Oral vascular malformations (VMs) are low blood flow vascular anomalies that present therapeutic challenges, often requiring minimally invasive approaches. This study aims to evaluate, through a comprehensive literature review, the clinical effectiveness of sclerotherapy and FDIP in managing VMs in the oral cavity, particularly regarding lesion volume reduction and symptomatic relief. This narrative review examined the clinical outcomes of sclerotherapy and forced dehydration with induced photocoagulation (FDIP) in the treatment of oral VMs. A total of ten studies published between 2014 and 2024, encompassing 2,120 patients, were included. The lower lip, tongue, and buccal mucosa were the most affected sites. Monoethanolamine oleate (5%) and polidocanol, particularly in foam form, were the most effective agents, yielding high rates of lesion regression with low complication rates. Pingyangmycin/Bleomycin showed promising results, especially in combination with electrochemical therapy, while sodium tetradecyl sulfate demonstrated lower efficacy but favorable safety. FDIP emerged as an effective alternative, though its broader use is limited by cost. The findings support sclerotherapy as a first-line, safe, and effective treatment for low-flow oral vascular malformations.